Mixed-Age Group Teaching in Second Language Learning: An Observational Study of a Montessori Classroom in Pakistan - Asma Shahid Kazi, Shagufta Moghal, Fakhra Aziz (JECCE, 2023)
This study aimed to highlight the effects of teaching young students of 3 to 6 years in mix aged groups, especially in language learning. The mixed method study employed purposive sampling, where observations of a class with 40 students, and semi-structured interviews of 2 Montessori Directresses were the chosen mode of investigation. The setting of the classrooms and the nature of the interactions and exchanges among the mix aged students creates an almost familial environment, where the older students take on the roles of mentors and help younger students learn and correct their errors. The participants asserted that there was seldom any conflict or clash of interests in the Montessori classroom, as the energies of all students were engaged positively. The observations also showed that peer interactions and collaborative work in the group lessons and at the times of free student play, were contributing factors in second language acquisitions and learning the patterns of the new language inductively.